Ekstrak Daun Binahong Mencegah Kenaikan Kolesterol Darah pada Tikus yang Diberi Pakan Lemak Tinggi - Rahman, Asep Abdul; Kurniati, Neng Fisheri; Sukandar, Elin Yulinah (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Binahong (Anredera cordifolia (Ten.) v. Steenis) leaves empirically have been used to lower cholesterol levels. In this study, preventive activity of ethanol extracts will be tested on the animals fed with a high-cholesterol chow. Hypercholesterolemic animal model established by orally administering high-cholesterol chow, pure cholesterol, cholic acid, and propiltiourasil. The test animals were divided into 5 groups, including the positive control group, ethanol extract of binahong leaves at doses of 50 mg/kg bw, 100 mg/kg bw, and 200 mg/kg bw; and simvastatin at dose of 36 mg/kg bw. Extract was given at the same time as hypercholesterol induction. Lipid profiles were measured at the time before the induction, 15 days and 29 days after induction. Index of atherogenic was also calculated. The results showed that level of cholesterol and LDL of extract binahong at dose of 50 mg/kg (109.17±26.60 mg/dL and 55.78±23.92 mg/dL, respectively) had significant difference compared to a positive control group (p < 0.05). Furthermore, binahong extract at dose of 50 mg/kg bb had the lowest atherogenic index (0,68±0,27) and aorta thickening (150.60±41.72 μm) compared to other extracts at day 15 of induction. In conclusion, extract binahong at dose of 50 mg/kg bw rat gives the best effect to prevent the increase of cholesterol and LDL level on wistar male rats fed with a high-cholesterol chow.